Transparency and transferability of learning outcomes : a 20-year journey Analysis of developments at European and national level - (:unkn) unknown (Publications Office of the European Union, 2024)
"This report offers a comprehensive review of European policy initiatives (2000-20) aimed at improving learning outcome transparency and transferability, to support mobility and lifelong learning. Adopting a long-term perspective across education and training sectors, the study assesses policy coherence and impact. Findings reveal increasing synergies among initiatives, especially in terms of objectives and principles, supported by the adoption of the learning outcomes approach. However, opportunities for further European cooperation exist and could be strengthened, including across education and training sectors. Key contributions include a stronger emphasis on learning outcomes, increasing attention to learning outside formal settings, fostering policy alignment, promoting transparent qualifications, and advocating for flexible learning pathways" (author's abstract ; BIBB-DOKU)
Keywords: I 1.5 Internationale Organisationen & Institutionen; G 1.2.3 Qualifikationsentwicklungen; 370; EU-Bildungspolitik; Europäischer Qualifikationsrahmen; Europäisches Leistungspunktesystem; Qualifikationsrahmen; Qualifikationsnachweis; Lebenslanges Lernen; Learning Analytics